Addressing violence against children: A case review in the state of Qatar - Al-Mohannadi, Abdulla Saeed; Al-Harahsheh, Sanaa; Atari, Sajeda; Jilani, Nadeem; Al-Hail, Ghalya; Sigodo, Kennedy (Frontiers in Public Health, 2022)
Introduction Violence against children (VAC) is a critical public health issue that affects billions of children worldwide. The combination of its prevalence and severity of effects on children creates an urgent need for effective interventions. Multiple studies associate VAC with lifelong implications that affect children through adulthood. In Qatar, multiple approaches such as legislation are being used to protect children from all forms of violence. Despite the gravity of the issue, there is still low readiness for the prevention of VAC in Qatar. This review aimed to map approaches to addressing VAC in Qatar from the panelists' perspectives on current approaches to addressing VAC. Methods The review obtained data from a recorded video entitled “A Public Health Approach to Addressing Violence Against Children.” The panel discussion in this video clip was organized as a side event of the WISH virtual summit by UNICEF and WISH on World Children's Day, held in Qatar in November 2020. The video was transcribed and analyzed using thematic analysis. Findings It shows the importance of both global and national level interventions in addressing VAC. The review uses the socioecological model to show relationships among different levels of interventions addressing VAC in Qatar. The findings highlight the national approaches to addressing VAC using public health, and legislative and policy approaches. Discussion The interventions addressing VAC at different levels in Qatar are interconnected. Delineating each level is key to the formation of holistic interventions that leverage global, regional, national, communal, familial, and individual factors that support interventions to address VAC.